PENGEMBANGAN KOMPETENSI GURU MELALUI PELATIHAN PENELITIAN TINDAKAN KELAS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Afkar Ramadhani, Muhammad Syakhil; Abidin, Dindin; Faiz Ridlo, Azi (An-Nizam, 2024)
This study discusses the development of teacher competence through teacher training learners (PTK) and its impact on improving the quality of learning in the village of Karang Indah. Karang Indah village is an example of many rural areas in Indonesia that face the challenge of improving the quality of Education. PTK training is directed to improve teachers ' understanding of the latest curriculum, innovative learning methods, learning evaluation, classroom management, and application of technology in learning. The research method used is a case study with a focus on evaluating the impact of training on teacher learning practices and student achievement. The result of this training is an increase in the understanding and skills of teachers in conducting class action research and teachers realize the importance of innovation in learning the results of service activities in general, namely the teachers participating in the activity have understood and skilled in conducting class action research (PTK), and teachers have been skilled in preparing class action research articles. This activity is expected to improve the competence of teachers in teaching. Therefore, it is recommended that the government and educational institutions pay more attention to the development of teacher competence through PTK training, especially in rural areas such as Karang Indah Village.